The competitiveness of logistics providers invested by liner companies vs global 3rd party logistics providers (social and environmental aspects) - Aw, Shi Yun (Nanyang Technological University, 2021)
Liner companies have been investing in logistics service providers (LSPs) in the past years. With the investment, it can benefit and detriment the LSPs at the same time. Thus, making it unsure whether the investment will make LSPs more competitive or not. This paper looks into the rank between LSPs invested by liner companies and the global 3rd party logistics (3PLs). It also looks into the most vital key success factor (KSF) under the social and environmental aspects affecting the competitiveness of LSPs. LSPs invested by top five liner companies and top five global 3PLs are selected to study competitiveness in the social and environmental aspects. The survey results, input into the competitive strength assessment, showed global 3PLs is more competitive than LSPs invested by liner companies in general. LSPs invested by liner companies are stronger than global 3PLs in the social aspect, while the global 3PLs are stronger than LSPs invested by liner companies in the environmental aspect. The most vital KSF under social and environmental aspects affecting the competitiveness of the LSPs are ethical behavior KSF and green packaging KSF, respectively. Besides the most vital KSFs identified in the two aspects (i.e., social and environmental), employment KSF, and planning and operations KSF are also the KSFs that LSPs would like to focus on to ensure the continued competitiveness of the LSPs. The suggested ways of working on the employment KSF includes wide advertisement to reach out to potential employees and sending the employees to upgrade their skills to stay competency in the industry, with government funding. For the ethical behavior KSF, LSPs can have a code of business conduct and internal audits to ensure enforcement of the ethical practices. Corrective actions have to be done once there is any act against the code of business conduct. For the planning and operations KSF, LSPs and customers can work closely together with the use of software technology to have the optimal routing and schedule planned out to reduce the greenhouse gas (GHG) emissions. For the green packaging KSF, LSPs and the parties in the supply chain upstream (i.e., manufacturer) can use recyclable materials and reduce packaging wherever possible. They can also print the content of the material used for the green packaging onto the packaging, hence, allowing customers aware of the attentions LSPs are paying to the environmental issues.